2011
DOI: 10.1186/1471-2377-11-143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and favorable long-term outcomes for patients with idiopathic inflammatory myopathies: a retrospective single center study in China

Abstract: BackgroundLittle is known about the clinical features and true survival risk factors in Chinese Han population. We conducted the current study to investigate the clinical features, long-term outcome and true potential indicators associated with mortality of idiopathic inflammatory myopathies (IIM) in China.MethodsWe restrospectvely investigated 188 patients diagnosed with IIM at our hospital from January 1986 to April 2009. The primary outcome was determined with mortality. The secondary outcomes for survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
28
5
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 40 publications
7
28
5
11
Order By: Relevance
“…Our analysis showed a PM predominance of (32.14%), consistent with the American and European reports [21][22][23][24], and in contrast to a Chinese study [19], which showed a DM predominance.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our analysis showed a PM predominance of (32.14%), consistent with the American and European reports [21][22][23][24], and in contrast to a Chinese study [19], which showed a DM predominance.…”
Section: Discussionsupporting
confidence: 62%
“…This is in accordance with Arabian Studis in Riyadh and Jordan where the mean age of onset was 37.3 ± 16.3, and the female:male ratio was 2.7:1 and 34.3 ± 9.2 years, and female:male ratio was 1.7:1 [14,18] and differing from data reported by Chinese, [19] and Tunisian [20] studies showing higher ratio and mean age.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In our previous study, data showed that the Myositis Disease Activity Assessment Visual Analogue Scale (MYOACT) recommended by the international myositis outcome assessment collaboration study (IMACS) can be used to reliably evaluate disease activity in Chinese patients with PM/DM [14,15]. Therefore, we used the MYOACT to assess disease activity [15].…”
Section: Subjectsmentioning
confidence: 98%
“…Of the mortality features from our univariable analyses, those also described in adult IIM studies included older age at illness onset (46, 1013, 29), delay in diagnosis or treatment (4, 5, 10), ILD (6, 12–14), anti-synthetase autoantibodies (8, 9, 30) and dysphagia (6). Our study in JIIM did not identify other important mortality risk factors that have been seen in adult IIM, such as malignancy (4, 5, 1013), cardiac involvement and ischemic cardiovascular disease (6, 8, 11), skin ulcers (10, 13) and male gender (6, 11, 29). The presence of anti-SRP autoantibodies has been found to be a risk factor for death by some investigators (30), but not by others (31); anti-SRP autoantibodies did not appear to increase the risk of death in JIIM in our study.…”
Section: Discussionmentioning
confidence: 99%